CHARTING (Childern Smart Anti Sunting) : Inisiasi Gerakan Generasi Emas Bebas Stunting dan Peningkatan Kesehatan Masyarakat - Abdul Mahmud Yumassik; Hesti Febriyana Nurinsani; Nur Azizah; Reza Junadi; Riska Azizah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
The prevalence of nutritional problems among elementary school children in Indonesia is still high and prevalent. One of the nutritional problems, namely stunting, is caused by infectious diseases due to lack of Clean and Healthy Behavior (CHB). This service aims to provide education on various stunting prevention measures to create a stunting-free golden generation and improve public health. The sample used were elementary school children with a total of 67 children in 3 different schools with different activities. The implementation method consisted of several stages, namely, planning, field action in the form of socialization and demonstration, and the provision of pretest and posttest. The outcome of this activity is the improvement of knowledge and skills related to CHB as a prevalence of stunting nutritional problems measured by a questionnaire instrument (pretest and posttest). From this service, the community can provide education on anti-worm medication for children, the use of magnetic boards with replicas of various food examples and picture cards as learning media, the culture of consuming additional food besides daily staple food, and forming a clean lifestyle through dental, oral, and hand hygiene. The description of the data results based on the average pretest and posttest in the three sample schools shows an increase in knowledge related to nutritious and non-nutritious food and Clean and Healthy Behavior (CHB) in schools from 83% to 93% and Provision of Supplementary Feeding for School Children PMT-AS also increased from 82% to 100%.